THE CASE OF MIXED TICK-BORNE INFECTIONS – TICK-BORNE ENCEPHALITIS AND LYME DISEASE (B. GARINII, B. AFZELII) IN THE KEMEROVO REGION - Анатолий Васильевич Субботин; Данил Андреевич Этенко; Владимир Александрович Семенов; Мария Сергеевна Щербинина; Ванда Вацлавовна Погодина; Надежда Михайловна Колясникова; Сергей Валерьевич Мошнегуц; Татьяна Евгеньевна Бондаренко (Медицина в Кузбассе)
The article presents the analysis of the clinical case of development of chronic mixed TBE infection (TBE and ixodes tick-borne borreliosis) on the background of antibacterial therapy in an unvaccinated patient. For etiological verification were used ELISA assay methods, immunochip with fluorescence detection. In the diagnostic process was conducted EMG, CT and MRI studies. The patient had lesion brain and spinal cord caused by TBE infectious process, with B. garinii and B. afzelii. Conclusion. 1. The stable detection of TBE IgG antibodies at a high level indicates the absence of depression of humoral immunity in the application of the antibiotic Ceftriaxone. 2. A long term persistence of IgM antibodies in serum to Lyme disease, identification of the TBE antigen in serum and IgG antibodies in the cerebrospinal fluid of a patient, indicates incomplete elimination of the pathogen on the background of the therapy, causing the patient developed chronic mixed focal forms of TBE with latent form of ixodes tick-borne borreliosis. 3. Patient exhibits clinical symptoms of TBE (Epilepsy of Kozhevnikov).